PENGARUH PENGALAMAN AUDITOR, REPUTASI AUDITOR, PROFESIONALISME AUDITOR TERHADAP KUALITAS AUDIT (Studi Empiris Pada Kantor Akuntan Publik Di wilayah Kota Bekasi dan DKI Jakarta) - Adha, Safitri Namira; Istianingsih, Istianingsih; Mukti, Aloysius Harry (LPPM Institut Pendidikan Nusantara Global, 2024)
The Influence of Audit Experience, Auditor Reputation, Auditor Professionalism on Audit Quality. This research aims to measure the influence of auditor experience, auditor reputation, auditor professionalism on audit quality (empirical study at public accounting firms in the Bekasi City and DKI Jakarta areas). This research was conducted using a non-probability sampling approach with a purposive sampling method. The number of samples used in this research was 83 respondents. The design used in this research is hypothesis testing using Structural Equitation Model (SEM) - SmartPLS 4.0. The results of this research indicate that (1) Auditor experience has no effect on audit quality; (2) Auditor reputation has a positive effect on audit quality; (3) Auditor professionalism influences audit quality.